2020
DOI: 10.2147/jpr.s251948
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electroacupuncture Regulates Pain Transition by Inhibiting the mGluR5-PKCϵ Signaling Pathway in the Dorsal Root Ganglia</p>

Abstract: Background: Acute pain can transition to chronic pain, presenting a major clinical challenge. Electroacupuncture (EA) can partly prevent the transition from acute to chronic pain. However, little is known about the mechanisms underlying the effect of EA. This study investigated the effect of EA on pain transition and the activation of metabotropic glutamate receptor 5 (mGluR5)-protein kinase C epsilon (PKCε) signaling pathway in the dorsal root ganglia (DRG). Methods: The hyperalgesic priming model was establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
3
10
0
Order By: Relevance
“…However, there are few reports on whether EA regulates GABAAR expression or function in the peripheral nervous system. Here, we observed that EA treatment significantly prevented the prolonged hyperalgesia induced by PGE 2 injection following Car and decreased the expression of PKCε in the L4-L6 DRGs of hyperalgesic priming model rats, which is consistent with our previous report (Wang et al, 2020). Furthermore, EA upregulated the expression of GABAAR in the L4-L6 DRGs of hyperalgesic priming model rats.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, there are few reports on whether EA regulates GABAAR expression or function in the peripheral nervous system. Here, we observed that EA treatment significantly prevented the prolonged hyperalgesia induced by PGE 2 injection following Car and decreased the expression of PKCε in the L4-L6 DRGs of hyperalgesic priming model rats, which is consistent with our previous report (Wang et al, 2020). Furthermore, EA upregulated the expression of GABAAR in the L4-L6 DRGs of hyperalgesic priming model rats.…”
Section: Discussionsupporting
confidence: 92%
“…PKCεV1-2 (a specific PKCε antagonist) was intraplantarly injected into the ipsilateral paws of hyperalgesic priming model rats 10 min before the 2nd injection. PKCεV1-2 significantly inhibited the pain transition induced by Car/PGE 2 injection (Figure 3F, P < 0.05), which is consistent with previous studies (Wang et al, 2020). However, it failed to regulate the expression of GABAAR in the ipsilateral L4-L6 DRGs (Figure 3G, P > 0.05) but successfully inhibited the expression of PKCε (Figure 3G, P < 0.01).…”
Section: A Change In Gabaar Expression Is Involved In Pkcε Activationsupporting
confidence: 90%
See 3 more Smart Citations